Problem Structuring and Evaluation Integration - Onsel, Sule; Ulengin, Fusun; Topcu, Y. Ilker (Springer Berlin Heidelberg, 2000)
This study focuses on the integration of problem structuring with the evaluation of alternatives. The multiple criteria analysis is generally based on the latter with a hidden assumption that the problem is well defined with explicitly known criteria and alternatives. However, especially the strategic planning problems are ill-defined and, thus, the first step of the analysis must be concerned with the structuring of the problem before any careful evaluation of the alternatives is conducted. In this paper, the water crossing infrastructure selection problem is selected as a case study. The cognitive map derived through knowledge acqusition from 19 experts is converted into a hierarchical structure with the goal at the top and the alternatives at the bottom. At the second stage of the analysis, an expert system approach is used to transform tha data of the multiattribute problem into a manageable decision matrix according to the rules. Finally this matrix will be ready to proceed by any appropriate multiattribute method.